THE EFFECTIVENESS OF CINNAMON BARK EXTRACT PASTE (Cinnamomum burmanii) IN ELIMINATING Candida albicans IN THERMOPLASTIC NYLON - Gloria Meyana Sinaga; Rahmad Arifin; Sherli Diana; Ika Kusuma Wardani; Isyana Erlita (FKG ULM, 2024)
Background: One type of denture base that is widely used is thermoplastic nylon. Thermoplastic nylon not cleaned regularly will cause food residue to stick and give rise to fungi such as Candida albicans. Mechanical cleaning methods are more effective at removing microbes. However, regular toothpaste contains abrasive ingredients that can scratch dentures. Extracts from cinnamon bark can be used because they contain ingredients that can inhibit the growth of Candida albicans colonies. Purpose: To analyze the antifungal activity of using cinnamon bark (Cinnamomum burmanii) extract paste to eliminate Candida albicans on thermoplastic nylon. Methods: This research is purely experimental, using a pretest-posttest with a control group design. This study used 27 thermoplastic nylon plates measuring 65x10x3mm, which were divided into 3 groups, namely the cinnamon bark extract paste group with a concentration of 50%, Fresh 'n Brite paste as a positive control, distilled water as a negative control. Results: The results of the Kruskal-Wallis test show an effect based on treatment in each group. Conclusion: Fresh ‘n Brite denture paste as a positive control is more effective in eliminating Candida albicans on thermoplastic nylon than cinnamon bark extract paste with a concentration of 50% and distilled water as a negative control.